Awareness, treatment, and control of diabetes in South America: A systematic review and meta-analysis - Jorge Emerson Chachaima-Mar; Alexandra Isabel Ramirez Moreno; Kenjiro Chau Ruiz; Maria Lazo-Porras (Archives of Endocrinology and Metabolism)
ABSTRACT Theaim of this review is to determine the proportion of awareness, treatment, and control of diabetes in the South American region. A comprehensive search was conducted using PubMed, EMBASE, SCOPUS, and LILACS databases from January 1, 2014, to March 23, 2024. We included observational, population-based studies that assessed the rates of awareness, treatment, and control of diabetes. The risk of bias was evaluated as proposed by Hoy and cols. A meta-analysis was performed using the random effects model, and heterogeneity was assessed using the I2 statistic. Additionally, a metaregression analysis was conducted to further explore heterogeneity. Fourteen studies met our eligibility criteria. The disease awareness meta-analysis, which included six studies, revealed that 71.7% (95% CI: 65.2%-77.8%, I2: 94.2%) of participants had a previous diagnosis of diabetes. The disease treatment meta-analysis, which included five studies, indicated that 64.6% (95% CI: 52.9%-75.3%, I2: 98.7%) of participants were receiving some form of treatment for diabetes, and 42.4% (95% CI: 36.0%-49.1%, I2: 96.3%) had their glycemic values within target ranges. All included studies were assessed to have a low risk of bias. In South America, the limited available evidence suggests a significant portion of individuals with diabetes remain untreated and uncontrolled. Numerous countries lack critical information on the diabetes care cascade necessary to inform health policies.